Service catchment of mass rapid transit (MRT) feeder bus: a preliminary study of T461 route Taman Kajang Utama - Aida, Chloe Lim Jhin Lin; Ponrahono, Zakiah (Malaysian Institute of Planners, 2019)
The planning and development of rail services require various considerations. Land availability, land use, catchment, route matching, infrastructure fitting, barrier free and micro-climate friendly designs are some of the factors heeded prior to such installations. A deviation between designated and highly demanded service area in urban sprawl zones of the city has been occurring in many Malaysian cities. These gaps have led to the mismatch between origin/destination of passengers and planned locations of train stations and its feeder bus stops. As such, rail services become less accessible to populations with the highest demands. This paper discusses the preliminary findings from a pilot study which seeks to calibrate the research instrument and validate preliminary findings before actual data collection for the purpose of determining the service catchment of the T461 feeder bus in Kajang MRT Station. The Garmin GPS device acts as the research instrument to obtain coordinates of locations where passengers board and alight feeder buses. On-board surveys and comparison analyses are methods that have been used to obtain the optimum GPS coordinates of the bus stop locations. The preliminary findings indicate that the research instrument is ready to be used for actual data collection and geospatial analysis to determine the service catchment of the T461 feeder bus service.